ANALYTICAL AND NUMERICAL MODELING WITH THE COMPUTER PROGRAMS MATLAB AND MAPLE - Apeināns, Ilmārs; Kangro, Ilmārs (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2017)
The author in this work provides insight into the analytical and numerical modeling of natural phenomena, systems and devices As mathematical modeling can be devided in to two different sub-types. Author worked with both, analytical and numeritical, to provide better insight in this topic.